Efficient propagation of an important medicinal plant boesenbergia rotunda by shoot derived callus - Yusuf, N.A.; Annuar, M.S.M.; Khalid, N. (2011)
A protocol for high frequency shoot organogenesis and plant establishment from shoot base derived callus was developed for Boesenbergia rotunda (L.) Mansf. Kulturpfl. The cultures produced callus in MS medium supplemented with various concentrations of dicamba and 2,4-D. Nevertheless, embryogenic callus only emerged on 2, 4-D augmented MS medium. In addition, the success of callus induction was achieved from meristem derived callus producing 100 of embryogenic callus. Multiple shoot induction was achieved from the surface of the callus after transferring onto MS medium supplemented with BAP or kinetin (shoot induction medium). The highest frequency of callus producing shoots (49.8) was achieved on MS medium containing 2.0 mg/L BAP. Plantlets with welldeveloped shoots and roots on MS medium supplemented with 2 g/L activated charcoal were acclimatized and successfully grown in the greenhouse.